PENGARUH LINGKUNGAN KERJA FISIK DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT SUMBER ALFARIA TRIJAYA TBK CABANG PARUNG BOGOR - Arsita Yuniarsih; Arsita Yuniarsih (JURNAL KONSISTEN, 2024)
Purpose. This research aims to determine the role of the Physical Work Environmentand Work Motivation on Employee Performance both partially and simultaneouslyMethods. This research method uses the Descriptive Quantitative methodResults. The t (partial) test results between work environment variables to employee performance show the value of count > ttabel (15,557 > 1,994) and sig < 0.05 (0.000 < 0.05) so that Ho is rejected and Ha is accepted, meaning that there is a significant positive relationship or influence between the physical work environment and employee performance. The t (partial) test results between work motivation variables against employee performance show the value of the count > ttabel (15,752 > 1,994) and sig < 0.05 (0.000< 0.05) so that Ho is rejected and Ha is accepted, meaning that there is a significant relationship or positive influence between work motivation and employee performance. The results of simultaneous testing between work environment variables and work motivation show that the value of Fhitung 208,460 > Ftable 3,13 or the sig value of 0.000<0.05 then Ho is rejected and Ha is accepted, then the research results show that there is a significant positive influence between the physical work environment and simultaneous work motivation on employee performance at PT Sumber Alfaria Trijaya Tbk Bogor Parung Branch.Implications. The results of simultaneous testing between work environment variables and work motivation show that the value of Fhitung 208,460 > Ftable 3,13 or the sig value of 0.000<0.05 then Ho is rejected and Ha is accepted, then the research results show that there is a significant positive influence between the physical work environment and simultaneous work motivation on employee performance at PT Sumber Alfaria Trijaya Tbk Bogor Parung Branch.